2017
DOI: 10.18632/oncotarget.14726
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs in osteosarcoma

Abstract: Long non-coding RNAs (lncRNAs) with more than 200 nuleotides, have been explored to participate in various cancer types including osteosarcoma (OS), which is the most common kind of primary bone tumors with high morbidity in infants and adolescents. These oncogenic or tumor suppressive lncRNAs regulate OS pathogenesis, such as cell growth, proliferation, invasion, migration, metastasis and cell apoptosis, serve as independent prognostic biomarkers or play a significant role in multidrug resistance (MDR) in OS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
69
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 104 publications
0
69
1
Order By: Relevance
“…Long noncoding RNAs (lncRNAs) are a class of non‐protein‐coding molecules longer than 200 nucleotides that are involved in the development and progression of human cancers including osteosarcomas . In the past few years, many lncRNAs have been shown to be an oncogene or antioncogene such as TUG1 , ZEB1‐AS1 , SPRY4‐IT1 , H19 , BCAR4 , and MFI2 .…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are a class of non‐protein‐coding molecules longer than 200 nucleotides that are involved in the development and progression of human cancers including osteosarcomas . In the past few years, many lncRNAs have been shown to be an oncogene or antioncogene such as TUG1 , ZEB1‐AS1 , SPRY4‐IT1 , H19 , BCAR4 , and MFI2 .…”
Section: Introductionmentioning
confidence: 99%
“…Even though more and more lncRNAs have been reported to play crucial roles in osteosarcoma [15, 17, 21], the roles of lncRNAs in osteosarcoma are remain poorly defined. The identification of osteosarcoma-associated lncRNAs was needed to better understand the initiation and progression of osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that lncRNAs interact with nucleic acids or proteins in diverse biological processes, including cell proliferation, cell differentiation, chromatin remodeling, and drug resistance [9-11]. Previous studies have shown that lncRNAs could act as oncogenes or tumor suppressors during the development and progression of cancers, such as hepatocellular carcinoma, lung cancer, pancreatic cancer, osteosarcoma, and colon cancer [12-17]. For example, lncRNA DGCR5 was decreased in hepatocellular carcinoma tissues and serum, and low DGCR5 expression was associated with HbsAg and vascular invasion.…”
Section: Introductionmentioning
confidence: 99%
“…These potential biomarkers predictive of survival or response to therapy will be helpful to guiding the individualized treatment of osteosarcoma patients and finally improve their outcome. In recent years, studies have demonstrated that lncRNAs are involved in various biological processes of osteosarcoma, including progression and metastasis, and aberrant expression of multiple lncRNAs was found to have the potential value for predicting outcome of osteosarcoma patients [37,38].…”
Section: Discussionmentioning
confidence: 99%